Investigation of physicaland mechanical properties ofbronzealloying elements - Түсіпжaнов А.Е.; Әлихaн Ж.; Кaнтaй Н.; Бектaсовa Г.С. (Recent Contributions to Physics, 2016)
At present, the international communitypaid special attention to new technologies and materials, in engineering and aviation industries. Therefore, one of the priorities of the Materialsis, improve performance and reduce the cost of materials used. In The article studied the physical and mechanical properties of the bronze with addition of alloying elements. Investigations of mechanical properties of the modified bronze in the initial state and after heat treatment. The studies revealed that in the initial state bronze has a face-centered cubic lattice, and after rolling appears tetragonal CuAl2 secondary phase. The microhardness of the sample with the Ni, Pb and La alloying elements increasing by 94%, but the phase changes on X-ray diffraction did not reveal. Investigation of the structure on a scanning electron microscope shows that there is an allocation of secondary phases along grain boundaries.